Safety and Immune Effects of Blocking CD40 Ligand in Multiple Sclerosis. Issue 6 (15th November 2021) - Fadul, Camilo E.; Mao-Draayer, Yang; Ryan, Kathleen A.; Noelle, Randolph J.; Wishart, Heather A.; Channon, Jacqueline Y.; Kasper, Isaac R.; Oliver, Brant; Mielcarz, Daniel W.; Kasper, Lloyd H.
Abstract : Background and Objectives: Costimulation by CD40 and its ligand CD40L (CD154) is important for the functional differentiation of T cells. Preclinical studies have recognized the importance of this costimulatory interaction in the pathogenesis of experimental models of multiple sclerosis (MS). To determine safety, pharmacokinetics, and immune effect of a humanized monoclonal antibody (mAb) against CD40 ligand (toralizumab/IDEC-131) in patients with relapsing-remitting MS (RRMS). Methods: This single-institution open-label dose-escalation study (phase I) enrolled 12 patients with RRMS to receive 4 doses of 1, 5, 10, or 15 mg/kg of humanized αCD40L (toralizumab) IV infusion every other week. Patients were followed up to 18 weeks, annually, and finally at 5 years. In addition to safety and pharmacokinetics, other secondary and exploratory measurements are immune effects, clinical, MRI, laboratory, and neuropsychological evaluations. Results: Fifteen adverse events, all of mild to moderate severity, were considered to be of possible or of unknown relationship to treatment. No serious adverse events, including thromboembolic events, occurred during the 18-week defined study period. Annual and long-term follow-up at 5 years revealed no delayed toxicity. Pharmacokinetics were nonlinear between the 5 and 10 mg/kg dose groups. The serum half-life of toralizumab was consistent between the dose groups with a mean of 15.3 days (SD = 1.9). Flow cytometry revealed no depletion of lymphocyte subsets. An increase in the CD25+/CD3+ and CD25+/CD4+ ratio and a shift toward an anti-inflammatory cytokine response were seen after treatment. Discussion: Our study suggests that blocking CD40L is safe and well tolerated in patients with RRMS while increasing CD25 + T cells and anti-inflammatory cytokine profile. These findings support further studies to assess the efficacy of blocking CD40L as a potential treatment of RRMS. Classification of Evidence: This study provides Class IV evidence on the safety, pharmacokinetics, and immune effects of an mAb to CD40L in patients with RRMS.